2022
DOI: 10.1186/s12889-022-14372-6
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and factors associated with food insecurity in eight high-altitude cities in Peru during the second wave of the COVID-19 pandemic: a retrospective, cross-sectional study

Abstract: Background Food insecurity has increased during the COVID-19 pandemic, affecting an estimated 260 million people. However, little evidence is available on how pandemic-related characteristics influence food security in a high-altitude population. The objective of this study was to assess factors associated with food insecurity in high-altitude Peruvian cities during the second epidemic wave of COVID-19. Methods A retrospective, cross-sectional stud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 41 publications
1
7
0
Order By: Relevance
“…Another study found that households with more rooms in urban areas were less likely to experience food insecurity, a finding that was possibly related to the socioeconomic level of the household ( 30 ). A study conducted in eight cities in Peru reported that people who lost their jobs during the pandemic had an 82% higher prevalence of food insecurity, which could be due to the greater reduction of the labor force in that country during the year 2020 ( 31 ), a result that is consistent with our results.…”
Section: Discussionsupporting
confidence: 91%
“…Another study found that households with more rooms in urban areas were less likely to experience food insecurity, a finding that was possibly related to the socioeconomic level of the household ( 30 ). A study conducted in eight cities in Peru reported that people who lost their jobs during the pandemic had an 82% higher prevalence of food insecurity, which could be due to the greater reduction of the labor force in that country during the year 2020 ( 31 ), a result that is consistent with our results.…”
Section: Discussionsupporting
confidence: 91%
“…The four last elements ask about satisfaction with current sleep, others' perception of the participant's current sleep problem, concern about sleep, and interference of sleep problems with daily functioning (46). It has a score from 0 to 28 points, which is interpreted as follows: insomnia absence (0-7), subthreshold insomnia (8)(9)(10)(11)(12)(13)(14), moderate insomnia (15)(16)(17)(18)(19)(20)(21), and severe insomnia (22)(23)(24)(25)(26)(27)(28). It has an acceptable internal consistency of 0.7 (45).…”
Section: Insomnia Severity Indexmentioning
confidence: 99%
“…Since the onset of the COVID-19 pandemic, it has posed a threat to both physical ( 1 4 ) and psychological health ( 5 14 ). This impact, coupled with its effects on social and economic aspects, has had far-reaching consequences on the safety and overall well-being of the population ( 15 , 16 ).…”
Section: Introductionmentioning
confidence: 99%